Mathematical Modelling for Predicting the Performance of Photovoltaic Modul - Md Sabudin, Siti Nurashiken; Norazaliza, Mohd Jamil; Saifful Kamaluddin, Muzakir (Akademi Sains Malaysia, 2020)
The demand for photovoltaic (PV) system is growing rapidly driven by technological development and awareness of green environment. A photovoltaic system converts the energy of light into electricity without emission of harmful by-product. A complete PV system consists of a solar panel (which combination of few solar cells), Pulse Width Modular (PWM) and a battery. Eight photovoltaic parameters are used to characterized the quality and efficiency of a PV module i.e (i) short circuit current (ISC), (ii) open circuit voltage (VOC), (iii) Theoretical Power (PT), (iv) maximum power (PMAX), (v) voltage at PMAX (VMPP) , (vi) current at PMAX (IMPP), (vii) fill factor (FF) and (viii) efficiency (). The PV parameters of laboratory scale solar cell could be determined based on current-voltage (I-V) and power-voltage (P-V) curves which could be plotted using a combination of solar simulator and a potentiostat instruments. Two additional PV parameters i.e (i) reverse saturation current of diode (IRC) and (ii) photocurrent (IPV) have been studied intensively as input of mathematical models to simulate and determine the quality and efficiency of solar cells. However, reproduceable results and robust mathematical models are yet to be established. A mathematical model employing the IRC, IPV and diode ideality factor (a) – which received lack of focus by previous researchers; is proposed. We have validated the mathematical model by comparing the calculation I-V and P-V curves results with the specifications established by the manufacturer. We have conducted three studies based on different specification of silicon based solar module i.e (i) 300W, (ii) 265W and (iii) 250W to obtain temperature distributions and average solar irradiance at selected locations. Through a comparative analysis, the theoretical calculation results and the manufacturers’ specifications are in good agreement.